SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN SUPPLIER INFRASTRUKTUR IT ( Studi Kasus: PT.CIPTA KARYA KOMPUTER ) - Ahmad Fauzi (Universitas Bina Sarana Informatika Kota Sukabumi, 2016)
Decision-making is the selection of several alternative measures exist to achieve one or more goals or intentionswhich have been determined (Turban, 2005). Problems occur if there is a decision support not as expected and thelack of objectivity in decision making. Fuzzy Multi Attribute Decision Making (F-MADM) is a decision supportsystem is quite simple and can be one of the alternative methods of making decisions if alternative or variables thatare used quite a lot. In this study, the research done to make the selection of the supplier of IT infrastructure byusing Analytical Methods Hierarcy Process (AHP) where this method would use the factors that have been there inaccordance with the provisions of the company, the existing criteria will be sought priority of each criterion todetermine which is more important criteria. Decisions can be taken based on the results of stimuli respondents, byadministering a questionnaire containing a comparison between the criteria and alternatives as a test (Supplier)about the decisions involved in choosing the supplier. And by using the tools expert choice in 2000 in dataprocessing with Hierarcy Analytical Method Process (AHP). The end result of this research puts PT.BuanaGloblindo Consistent with the weight of 47.2%, CV.Brianco Main Partners with weights of 29.3%, and PT.TelecomVisitama with a weight of 23.5%. The highest ranking in the selection of suppliers of raw materials are those whichhave the greatest weight.